Methods of sociolinguistic lexicometry: analysis of the contemporary oral corpus PRESEEA-Santander - Martínez Martínez, Inmaculada; Ueda, Hiroto (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Lexicometry is a method that allows us to identify thematic units derived from the automatic extraction of knowledge patterns in data of a textual nature (Romero, Alarcón and García, 2018). From its application, the lexical tendencies of a corpus emerge through the quantification of the occurrence of words. The different sociolinguistic lexical styles have been studied in wide varieties of the world’s languages, including the Spanish language. However, in the studies available to us to date, there are not enough quantitative analyzes of the lexicon of a contemporary oral sociolinguistic corpus. The general objective of this article is to detect the preferences for the use of the vocabulary of the spoken Spanish language within the framework of sociolinguistic lexicometry. To do this, a representative sample of a corpus with stratification in three variables (sex, age, educational level) was analyzed. This sample belongs to the PRESEEA-Santander corpus, framed in the Project for the Sociolinguistic Study of Spanish in Spain and America (Moreno Fernández, 2021). The LYNEAL system (Letters and Numbers in Linguistic Analysis) (Ueda, 2021) was used in the analysis, as well as the open-source statistical software R. The results indicate that gender is revealed as an important variable in the process of lexical variation, detecting, among other findings, the use of nominal over verbal style and the preferential use of adverbs in -mente by men; with respect to age, the tendency to use lexical truncation in the younger generation and in the female gender is noted; finally, the concentration of use of muchísimo in women, young people, with a primary education level, is appreciated.